Основы средневекового китайского права (VII-XIII вв.) - Кычанов Евгений Иванович (Наука, 1986)
Экземпляры: КХ (20210730) / Инвентарный номер: 884823 / Сис.шифр: 34И / Авт.знак: К 97 / ГРНТИ: 10 / ББК: 67